MELALUI METODE DISKUSI DENGAN MEDIA GAMBAR SERI DAPAT MENINGKATKAN KETERAMPILAN MENGARANG SISWA KELAS IV SDN 5 PRABUMULIH - Sari, Diana Paristhy; Samosir, Hendro TG; Oktarina (STKIP Pesisir Selatan, 2023)
The purpose of this study was to determine the success or failure of using the picture series media discussion method to improve the writing skills of fourth grade students at SDN 5 Prabumulih semester 2 of the 2022/2023 academic year. The research method used was classroom action research with 26 students as research subjects. There are four stages of activity in each cycle: preparation, action, observation, and results of reflection. The results showed that the writing skills of fourth grade students at SDN 5 Prabumulih could be improved by using the discussion method using picture series media. According to cycle I, the number of students who completed 12 students or 46.15% and the number of students who did not complete 14 students or 53.85%. The results of cycle II increased with the number of students completing around 24 students or 92.30% and students not completing 8% or around 2 students. From these data it can be concluded that using the discussion method using picture series media can improve the writing skills of class IV students at SDN 5 Prabumulih.